EVALUASI PRODUKSI DAN KUALITAS SEMEN SAPI SIMMENTAL TERHADAP TINGKAT BOBOT BADAN BERBEDA - Fitrah Khairi (State Islamic University of Sultan Syarif Kasim Riau, 2016)
This study was conducted to find the rate of body weight ideal study Simental cows to produce production and the best quality fresh semen. The material used in this study were 9 males Simental cows were divided into 3 ranges of body weight as a treatment that is P1 = low body weight (822-878 kg), P2 = moderate weight (910-958 kg) and P3 = body weight high (983-1041 kg). The number of cows in each group of body weight is considered as replicates. The method used was a survey method. The research is designed to completely randomized design (CRD) with 3 treatments and weight range 3 replications. Each stud cows housed cement 2 times per week for 12 weeks so that each cow cement accommodated as many as 24 times. Parameters observed in this study is that the volume of fresh cement production of cement per shelter and semen quality bulls include sperm motility and concentration of spermatozoa. Data were analyzed using analysis of variance, followed by Duncan test if there are significant levels of different body weights. The results showed that differences in body weight bulls simental not significant (P>0.05) for fresh semen volume, sperm motility and concentration of spermatozoa. Mean semen volume is best found in the high body weight group, whereas sperm motility and concentration of spermatozoa present in body weight groups were.